PSORIATIC ARTHRITIS: AN ALGORITHM FOR MAKING A DECISION ON THE CHOICE OF MANAGEMENT TACTICS - N. A. Shostak (Klinicist, 2016)
Psoriatic arthritis (PA) is a chronic inflammatory disease of the joints, vertebral column, and entheses from a group of seronegative spondyloarthritides, which is observed in patients with psoriasis. In accordance with the 2013 federal clinical guidelines for the management of patients with PA, published by the Russian Society of Dermatovenereologists and Cosmetologists and the Association of Rheumatologists of Russia, its diagnosis should be based on the CASPAR criteria (ClASsification criteria for Psoriatic ARthritis, 2006). The activity of spondylitis in PA is assessed using the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) that is a questionnaire containing 6 questions; a numeric rating scale from 0 (“very good”) to 10 (“very bad”) scores is applied for a response. It is recommended that ultrasound studies and magnetic resonance tomography be used for the early diagnosis of enthesitis in seronegative spondyloarthritides. The Psoriasis Area Severity Index (PASI) that takes into account the area of the lesion, the magnitude of erythema, infiltration, and desquamation in different body areas. The early diagnosis of PA and the timely use of disease-modifying antirheumatic therapy are topical problems, as high-activity inflammation may lead to rapid joint destruction, physical limitations, and disability. When the signs of active PA (the presence of one or more swollen and tender joints, and/or 1 or more dactylitides, and/or more enthesitides and/or inflammatory back pain) are detected, prompt drug therapy is indicated. The clear compliance of the algorithm for making a decision on treatment policy and the timely assessment of the clinical manifestations of the disease improves prognosis, adherence to treatment, and quality of life.